What drives special dividend announcements?: An examination of macro perspectives - Hu, May (Financial Management, 2012)
This paper investigates macro-level explanations for why firms pay special dividends. The evidence shows that both market conditions and stages of the business cycle affect the propensity and abnormal returns of special dividend announcements. However, business cycle variations have economically larger impact on these events. Firms are more likely to announce special dividends in market or economic downturns rather than upturns. They tend to use additional cash for business growth in expansions and distribute it to reduce agency costs in contractions. The signalling effect of special dividend distributions is stronger and the companies with these announcements are better performers in recessions. This research sheds light on the reasons why we observe corporate events happening in waves and enhances the understanding of why firms disburse extra cash dividends at the aggregate level.